Results of application fragility index asd-fi for spinal surgery in elderly patients - Petrenko, Dmytro; Demchenko, Dmytro; Chekryzhev, Oleksandr; Kutz, Myhailo; Mezentsev, Andriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Identification of potential risks of complications before and after spinal surgery is one of the main task and challenge for the surgeon. That is why, modern health care system needs instruments for stratification of possible surgical complication. Objective: to assess results of Adult Spinal Deformity Fraility Index application in elderly patients after spinal surgery. Methods: we performed retrospective analyses of 38 cases in patients who underwent surgical intervention on the spine. Adult Spinal Deformity Fraility Index was assessed on the basis of diagnostic work-up, indication for surgery and existing comorbidities. If Adult Spinal Deformity Fraility Index was less then 0.3 patient was not frail, 0.3–0.5 meant frailty and more then 0.5 confirms severe frailty. In every group of patients American Society of Aneastesiologists scale and Oswestry Disability Index were estimated. Results: there were 27 complication in 12 patients (31.5 %) with relatively higher Adult Spinal Deformity Fraility Index score (over 0.4). Preoperative patient optimisation and appropriate surgical technique selection allowed to decrease number of complications in postoperative period. We found satisfactory correlation between Adult Spinal Deformity Fraility Index and Oswestry Disability Index score. Conclusions: Adult Spinal Deformity Fraility Index assessment allows to reveal group of high risk patients and to correct their condition to prevent potential complications. It is possible to reveal patients with contraindication for spinal surgery.